PENDEKATAN PEMBELAJARAN KETELADANAN DI TAMAN KANAK-KANAK (TK) TADIKA PURI JAKARTA SELATAN - Akhmad Shunhaji; Rini Komalasari (el-Moona: Jurnal Ilmu Pendidikan Islam, 2020)
Education at Tadika Puri Kindergarten, South Jakarta, is carried out using various approaches. A Role Models approach is the focus of this paper. Data were collected in the form of qualitative data with a phenomenological approach. Data is taken through direct observation during the learning period. Role Models learning in children is important. Children are impressionable individuals. Therefore, learning with an exemplary approach is the best choice for children. These results are consistent with the findings of observations at Tadika Puri Kindergarten, South Jakarta. Students experience an increase in good character after participating in the lesson. Pronouncing the words sorry, excuse me, please and thank you becomes a habit that is included in the practice of appropriate behavior